Study of SnO2 gels by Eu3+ fluorescence spectroscopy - Ribeiro, Sidney José Lima [UNESP]; Hiratsuka, R. S. [UNESP]; Massabni, A. M G [UNESP]; Davolos, Marian Rosaly [UNESP]; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Elsevier, 1992)
Eu3+ fluorescence spectroscopy was used as a probe to study the changes in local arrangements of tin oxyhydroxide precipitate → sol → gel → glass conversion. Electronic transition intensities and 5D0 excited state lifetime variations were followed during the entire process. Adsorption of Eu3+ ions on the colloid and changes of chemical interactions occurring in each step are described. © 1992 Elsevier Science Publishers B.V. All rights reserved.
Keywords: Fluorescence; Oxides; Spectroscopic analysis; Spectroscopy; Tin compounds; Electronic transition intensities; Fluorescence spectroscopy; Tin oxides; Gels